2002
DOI: 10.1124/mol.62.2.379
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Decreases G Protein-Coupled Receptor Kinase 2 in Lymphocytes via a Calpain-Dependent Mechanism

Abstract: G protein-coupled receptor kinase (GRK) 2 plays a crucial role in regulating the extent of desensitization and resensitization of G protein-coupled receptors (GPCRs). We have shown that the expression level of GRK2 in lymphocytes decreases during inflammatory diseases such as arthritis. Reactive oxygen species play an important role in a variety of inflammatory conditions, including arthritis. We demonstrate herein that oxidative stress, induced by exposure of lymphocytes to H 2 O 2 , results in a 50% reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 38 publications
0
46
0
Order By: Relevance
“…On the other hand, the platelet aggregation (induced by epinephrine) and reactivity are increased in depressed patients (García-Sevilla et al, 1986, 1990Musselman et al, 1996Musselman et al, , 2000, and activated platelets produce reactive oxygen species, such as hydrogen peroxide (Maresca et al, 1992) that can modulate the expression of GRKs. Thus, the exposure of lymphocytes to hydrogen peroxide resulted in marked decreases in GRK 2 expression and in agonistinduced desensitization of b 2 -adrenoceptors (Lombardi et al, 2002). This latter mechanism could also explain the observed decrease of GRK 2 and upregulation of a 2A -adrenoceptors in the platelets of depressed patients.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, the platelet aggregation (induced by epinephrine) and reactivity are increased in depressed patients (García-Sevilla et al, 1986, 1990Musselman et al, 1996Musselman et al, , 2000, and activated platelets produce reactive oxygen species, such as hydrogen peroxide (Maresca et al, 1992) that can modulate the expression of GRKs. Thus, the exposure of lymphocytes to hydrogen peroxide resulted in marked decreases in GRK 2 expression and in agonistinduced desensitization of b 2 -adrenoceptors (Lombardi et al, 2002). This latter mechanism could also explain the observed decrease of GRK 2 and upregulation of a 2A -adrenoceptors in the platelets of depressed patients.…”
Section: Discussionmentioning
confidence: 89%
“…For example, we have shown that in patients with rheumatoid arthritis or in rats after development of adjuvant arthritis or experimental autoimmune encephalomyelitis, the level of GRK2, 3, and 6 is reduced by 50 -80% in leukocytes from the blood or spleen (11)(12)(13). In addition, there is evidence that cytokines as well as oxygen radicals can regulate the level of expression of GRK in leukocytes and other cell types (11,14,15). Moreover, differentiation of the pro-myelocytic cell line HL-60 toward the neutrophil lineage results in increased expression of GRK6, suggesting a functional role for this GRK in PMN (9).…”
Section: P Olymorphonuclear Neutrophils (Pmn)mentioning
confidence: 99%
“…Briefly, 10 5 Ea.hy 926 endothelial cells were plated onto 24-well Transwells and incubated for 3 days. Monolayer integrity was determined by assessing diffusion of [ 14 C]mannitol (Amersham, Arlington Heights, IL) from the top chamber to the bottom chamber within the Transwell, and those Transwells in which the amount of 14 C cpm detected in the bottom well was Ͻ35% of control were used. The medium at the bottom was replaced with medium with or without LTB 4 and neutrophils were added to the top chamber.…”
Section: Chemotactic Assaymentioning
confidence: 99%
“…Specifically, activation of lymphocytes leading to increased intracellular calcium results in activation of calpains, causing increased degradation of GRK2. Decreased GRK2 levels result in reduced cytokine receptor desensitization (Lombardi et al, 2002). To date, similar information is not available regarding the regulation of GRK3.…”
mentioning
confidence: 99%